Superhydrophobic substrates allow the generation of giant quasi-static bubbles. (11th February 2021) - Rubio-Rubio, M.; Bolaños-Jiménez, R.; Martínez-Bazán, C.; Muñoz-Hervás, J.C.; Sevilla, A.
Abstract: Abstract : We report on experiments of the quasi-static growth and detachment of air bubbles in water from a superhydrophobic substrate, overcoming the maximum size limitation of conventional injectors due to the Rayleigh–Taylor instability. The observations are in good agreement with a hydrostatic model, demonstrating that bubbles grow through a sequence of quasi-equilibrium states. Our experiments corroborate the theoretical prediction of a maximum bubble volume of approximately $6.04 {\rm π}$ and a critical base radius of $3.22$, both numbers in units of the capillary length (Michael & Williams, Proc. R. Soc. Lond. A. vol. 351, 1976, pp. 117–127). This maximum is also reached when bubbles grow in an unbounded, ideally non-wetting surface, establishing the ultimate size limit of quasi-static bubble formation.